2016
DOI: 10.1167/iovs.16-19204
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pharmacokinetics of Intravitreal Aflibercept (Eylea) in a Rabbit Model

Abstract: Citation: Park SJ, Choi Y, Na YM, et al. Intraocular pharmacokinetics of intravitreal aflibercept (eylea) in a rabbit model. Invest Ophthalmol Vis Sci. 2016;57:261257: -261757: . DOI:10.1167 PURPOSE. We determined the intraocular pharmacokinetic properties of intravitreally injected aflibercept (Eylea) in a rabbit model. METHODS.Aflibercept was injected intravitreally in 21 eyes from New Zealand White rabbits. The eyes were enucleated 1, 24, 48, 120, 216, 360, and 720 hours (1, 2, 5, 9, 15, and 30 days, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 14 publications
9
58
0
Order By: Relevance
“…The intraocular PK of VEGF-Trap and FcfVEGF-Trap were evaluated using same experimental design as in our previous studies. [6][7][8][9] Intramuscular injection of 15 mg/kg Zoletil (a mixture of tiletamine and zolazepam; Virbac Laboratories, Carros, France) and 5 mg/kg xylazine, and a topical ophthalmic anesthetic (1% proparacaine hydrochloride, Alcaine; Alcon Laboratories, Inc., Fort Worth, TX, USA) were used for anesthesia. Eyes under investigation were dilated with eye drops containing a mixture of phenylephrine and tropicamide.…”
Section: Animal Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The intraocular PK of VEGF-Trap and FcfVEGF-Trap were evaluated using same experimental design as in our previous studies. [6][7][8][9] Intramuscular injection of 15 mg/kg Zoletil (a mixture of tiletamine and zolazepam; Virbac Laboratories, Carros, France) and 5 mg/kg xylazine, and a topical ophthalmic anesthetic (1% proparacaine hydrochloride, Alcaine; Alcon Laboratories, Inc., Fort Worth, TX, USA) were used for anesthesia. Eyes under investigation were dilated with eye drops containing a mixture of phenylephrine and tropicamide.…”
Section: Animal Studiesmentioning
confidence: 99%
“…5 In fact, it was previously reported that the vitreous half-life of ranibizumab (2.75 days) was shorter than those of bevacizumab (7.06 days) and aflibercept (3.63 days) in rabbits. [6][7][8][9] Intravitreally administered anti-VEGF drugs reach first and in a larger proportion in the external layer (pericytes) and then reach the inner layer (endothelial cells) after crossing the blood-retina barrier. 10 Recent studies reported that the elimination of intravitreally administered IgG across the blood-retina barrier into the systemic circulation is mediated by the neonatal Fc receptor (FcRn), which is expressed in the retinal pigment epithelium and endothelial cells of the retinal and choroidal vasculature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Increase in molecular size was reported to have a weak correlation with increase in residence time in the vitreous cavity. 21,22,23 A full-length 200 kDa DVD-Ig format with a larger molecular size was therefore selected for ABBV642. The third factor considered was safety.…”
Section: Design Considerations For Next-generation Treatments For Exumentioning
confidence: 99%
“…Although prolonged residence time in the eye is desirable, prolonged residence in systemic circulation is not because systemic suppression of VEGF is associated with hemorrhagic and thromboembolic complications. 24 The Fc neonatal receptor (FcRn) is responsible for prolonged serum residence, 25 but is not required for ocular 21,23 half-life of immunoglobulin molecules, and therefore FcRn binding was disabled in ABBV642 by introduction of a H435A (FcRn null) mutation. 26 Endothelial cells release paracrine PDGF-BB, which is retained proximally by heparin sulfate proteoglycan.…”
Section: Design Considerations For Next-generation Treatments For Exumentioning
confidence: 99%